Tramas da relação psicologia-educação: a proposta da rede municipal de Goiânia para a educação Infantil (2013-2016) - Lemos, Adriane Guimarães de Siqueira (2016)
That research, entered in the line Fundamentals of Processes Educational, investigates the vinculation psicology-education in the document Childhoods and Children in Scene: for one Politic of Infantile Education for the Rede Municipal de Goiânia (GOIÂNIA 2014). This is the qualitative research, bibliographic and documental, developed by content analysis procedure conducted from the strict document reading, the seizure of its structure and internal logic, the key concepts, and meanings and meanings of the terms and concepts used, based on the comparison with the appropriate theoretical framework in the literature review. By having for reference studies about the vinculation psychology-education from on one approach criticizes, based on historical analysis this relationship, it was found that it can take in order to hide and justify the unequal social relations and antagonistic and, concomitantly, support the training focused on the demands of the production process. It has been found that the principles identified in the document, the child who elected as centrality, and the emphasis on learning, for the organization and execution of educational processes, corroborates the movement here called webs of psychology-education relationship. The centrality of the child in the document is expressed by joining the Pedagogy of Childhood, the definition of the child as a subject of rights and the prominent place given to life experiences and experiences for the realization of the pedagogical proposal. The emphasis on learning is perceived in the document from the circumstantial teaching place, understanding that learning is a constitutive process and to the child and the subordination of this process to the interests and needs of the child. These are principles that historically are linked to the field of ideas psychology-education that tend to naturalization of the child and his formation.